Efektivitas Penerimaan Peserta Didik Baru (PPDB) Pada Jenjang SMA Negeri Kota Cirebon - Dicky Surahman; Endang Yuda Nuryenda (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
One of the annual compulsory activities carried out by every school to accept new students, namely the New Student Admission (PPDB), in implementing PPDB it is expected to eliminate schools labeled as favorite schools. The purpose of this study was to analyze the effectiveness of PPDB at the Cirebon City Senior High School. This study used a qualitative method, the research subjects were Class X Students of Cirebon City Senior High School taken by professional sampling with a total of 176 students. While the data analysis technique used in this study is a comparative descriptive analysis technique. The results of the study show the effectiveness of the admission of new students (PPDB) at the Cirebon City Senior High School which is very effective or has fulfilled 8 dimensions including (1) Availability of information systems; (2) The information system is easy to understand; (3) Relevant information system; (4) Useful information systems; (5) Timely information system; (6) Reliable information systems; (7) Accurate information system; and (8) Information systems must be consistent